2007
DOI: 10.1007/s10637-007-9087-y
|View full text |Cite
|
Sign up to set email alerts
|

NK-1 receptor antagonists induce apoptosis and counteract substance P-related mitogenesis in human laryngeal cancer cell line HEp-2

Abstract: It has been demonstrated that substance P (SP) induces cell proliferation and neurokinin-1 (NK-1) receptor antagonists inhibit growth in several human cancer cell lines, but it is currently unknown whether such actions are exerted on human laryngeal carcinoma cell line HEp-2. In addition, the presence of NK-1 receptor has not been demonstrated in this cell line. We carried out an in vitro study of the growth inhibitory capacity of the NK-1 receptor antagonists L-733,060 and L-732,138 against human laryngeal ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
72
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 74 publications
(83 citation statements)
references
References 36 publications
10
72
0
1
Order By: Relevance
“…5 It has also been shown that activation of NK-1 receptors by SP induces mitogenesis in several melanoma cell lines 6,7 and others tumor cell lines. [8][9][10][11][12][13][14][15][16] SP is also a main mediator in the growth of capillary vessels in vivo and in the proliferation of cultured endothelial cells in vitro, and it has also been shown that NK-1 receptor agonists induced neoangiogenesis. 17 Moreover, the active migration of tumor cells, a crucial requirement for invasion and metastasis, is regulated by SP signals.…”
mentioning
confidence: 99%
“…5 It has also been shown that activation of NK-1 receptors by SP induces mitogenesis in several melanoma cell lines 6,7 and others tumor cell lines. [8][9][10][11][12][13][14][15][16] SP is also a main mediator in the growth of capillary vessels in vivo and in the proliferation of cultured endothelial cells in vitro, and it has also been shown that NK-1 receptor agonists induced neoangiogenesis. 17 Moreover, the active migration of tumor cells, a crucial requirement for invasion and metastasis, is regulated by SP signals.…”
mentioning
confidence: 99%
“…(a) by inhibiting tumor cell proliferation in several tumor cell lines, including breast cancer cells [10,13,14]. NK-1 receptor antagonists induce cellular death by apoptosis [10,14]; (b) by inhibiting tumor neoangiogenesis [15]; and (c) by inhibiting the migration of tumoral cells (e.g., breast carcinoma cells) [9,16].…”
Section: Nk-1 Receptor Antagonists Exert An Antitumor Actionmentioning
confidence: 99%
“…NK-1 receptor antagonists induce cellular death by apoptosis [10,14]; (b) by inhibiting tumor neoangiogenesis [15]; and (c) by inhibiting the migration of tumoral cells (e.g., breast carcinoma cells) [9,16]. NK-1 receptor antagonists also block the mitogenic action exerted by SP on tumor cells.…”
Section: Nk-1 Receptor Antagonists Exert An Antitumor Actionmentioning
confidence: 99%
See 2 more Smart Citations